MINERALS, NUTRIENTS AND ACTIVE COMPOUNDS OF RAMBUTAN FRUITS - Sukemi - (PROSIDING SEMINAR KIMIA, 2014)
The main object ive of this essay was to describe the minerals, nutrients and active compounds of rambutan (Nephelium lappaceum L.) fru its. Flesh fruit of rambutan is a source of minerals and ascorbic acid that are needed by human body. Its seed oil provides mineral and fatty acid. Its peel contains ellagic acid, corilagin and geraniin that have biological activit ies, such as antioxidant, anticancer, anti-inflammation, anti-hyperalgesic antiviral, anti-semicarbazide-sensitive amine o xidase (SSAO), and anti-hypertensive. Rambutan is not only consumed as fresh fruits, but also it can be used as sources of food and medicine products.